Functional Outcome of Medial Patello-femoral Ligament Reconstruction in Recurrent Patella Dislocation using Semitendinosus tendon auto-graft. (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the functional outcome of medial patella-femoral reconstruction in recurrent patella dislocation using Semitendinosus tendon auto-graft and cross-tunnel technique.Methods: This descriptive study was conducted in Orthopaedic department Liaquat National Hospital Karachi from 16th October 2016 to 20th October 2021. Patients of both gender and age 18 to 45 years with recurrent patella dislocation fulfilling the inclusion criteria were enrolled in this study. The recurrent patella dislocation was treated with medial patella-femoral ligament reconstruction(MPFL) with a novel technique using the semitendinosus tendon auto-graft that was tunneled into the patella and fixed onto the distal femur. Post operative functional outcome at one year was assessed with International Knee Documentation Committee scores (IKDC). Comparison between pre-operative and post-operative IKDC score was done with non-parametric Wilcoxon signed-rank tests and parametric t test for dependent variables. P value < 0.05 was considered significant.Results: The total number of patients were 48 patients with mean age 24.2 ± 11.4 years. Male patients were 17(35.4%) and female 31(64.6%). Isolated MPFL injury was present in 29 (60.4%) patients while MPFL and medial Meniscal injury was noted in 19 (39.6%). Right sided recurrent patella dislocation was noted in 30(62.5%) and left sided in 18(37.5%) patients. The mean IKDC score improved from pre operative value of 42.4 ± 9.3 to post operative 86.3 ± 12.6 at one year follow up(p?0.05). No statistically significant difference in the functional outcome was noted between gender, side of injury and MPFL reconstruction with and without Meniscal injury(p >0.05)Conclusion: Medial Patellofemoral ligament(MPFL) reconstruction using Semitendinosus tendon auto-graft and cross-tunnel technique is a novel surgical technique for recurrent patella dislocation as excellent functional outcome has been achieved in majority of our patients. We recommend this technique as operation of first choice for recurrent patella dislocationin selected patients.